2010
DOI: 10.2460/ajvr.71.7.720
|View full text |Cite|
|
Sign up to set email alerts
|

Analgesic effects of tramadol hydrochloride administered via caudal epidural injection in healthy adult cattle

Abstract: Caudal epidural tramadol administration induced analgesia with slight to mild sedation and ataxia in cows. Analgesia in affected regions after administration of 2 or 3 mg of tramadol/kg was considered sufficient to allow common surgical procedures to be performed in standing cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
0
8
0
6
Order By: Relevance
“…Intravenous medication may cause safety problems, such as respiration depression (Yaster and Nichols, 2001;Mantadakis et al, 2009;Batra et al, 2010), while local anesthesia in lumbar punctures may not work due to patients' crying (Committee on Drugs and American Academy of Pediatrics, 2002;Draisci et al, 2009;Baniadam et al, 2010;Shadangi et al, 2011). Propofol is an intravenous anesthetic commonly used clinically, which is quickly effective and easily controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous medication may cause safety problems, such as respiration depression (Yaster and Nichols, 2001;Mantadakis et al, 2009;Batra et al, 2010), while local anesthesia in lumbar punctures may not work due to patients' crying (Committee on Drugs and American Academy of Pediatrics, 2002;Draisci et al, 2009;Baniadam et al, 2010;Shadangi et al, 2011). Propofol is an intravenous anesthetic commonly used clinically, which is quickly effective and easily controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Caudal epidural tramadol administration has been performed in different species such as horses (Natalini & Robinson, 2002), cattle (Baniadam et al, 2010;Bigham et al, 2010), sheep (Habibian et al, 2011), goats (Dehkordi et al, 2012), cats (Castro et al, 2009) and dogs (Guedes et al, 2005;Natalini et al, 2007). However, to the authors' knowledge, this is the first study to investigate the analgesic effect of epidural administration of tramadol (monotherapy) in camels.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Elghazali et al (2008), no drug-associated adverse effect was observed following intravenous and intramuscular tramadol in camels. According to the studies performed in cattle (Baniadam et al, 2010), horses (Natalini & Robinson, 2002), donkeys (Faleiros et al, 2004) and dogs (Guedes et al, 2005), epidural tramadol had no effect on HR, RR and RT. However, based on the results of the present study, there was an increase in HR, RR and RT in the first 15 to 30 min of the experiment and soon after that, the increasing trend stopped.…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation
“…A utilização de analgésicos opioides, como alternativa para o manejo de dor em bovinos, ocorre, principalmente, através da via de administração epidural (5) . Contudo, a aplicação sistêmica destes fármacos é limitada a poucos princípios ativos como a morfina, meperidina, buprenorfina e butorfanol (6) .…”
unclassified